2014
DOI: 10.1002/2013sw000967
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of GIC risk due to geomagnetic sudden commencements and identification of the current systems responsible

Abstract: During periods of enhanced geomagnetic activity, geomagnetically induced currents (GIC) flow in power systems potentially causing damage to system components or failure of the system. The largest GIC are produced when there are large rates of change of the geomagnetic field (dB/dt). It is well established that the main phase of a geomagnetic storm, particularly the magnetic substorms occurring during that period, is a cause of large GIC and hence a risk factor for power systems. However, some power system dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 49 publications
2
97
0
Order By: Relevance
“…7 and 8 are shifted 14 min for C03 and 25 min for C05 in order to make the interplanetary shock and the SC coincident). Indeed, southward abrupt reversals have been identified as the cause of prompt electric field penetration (Ohtani et al 2013), which is favoured by high solar wind density/pressure (Lopez et al 2004;Fiori et al 2014). The end of each drop in H (the peak of the spike) is well correlated to a northward IMF turning as well.…”
Section: Discussionmentioning
confidence: 99%
“…7 and 8 are shifted 14 min for C03 and 25 min for C05 in order to make the interplanetary shock and the SC coincident). Indeed, southward abrupt reversals have been identified as the cause of prompt electric field penetration (Ohtani et al 2013), which is favoured by high solar wind density/pressure (Lopez et al 2004;Fiori et al 2014). The end of each drop in H (the peak of the spike) is well correlated to a northward IMF turning as well.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent analysis, Fiori et al (2014) reported data that support these estimates. Note, however, that Tsurutani and Lakhina (2014) estimated a maximum SC-type dB/dt = 30 nT/s on a 22 s timescale, from a different point of view.…”
Section: Sc-type Transient Gicsmentioning
confidence: 90%
“…While the vast majority of GIC studies focus on severe geomagnetic storms, such space weather phenomenon as the SC can also produce very large dB∕ dt at various latitudes, from an auroral region to the geomagnetic equator (Fiori et al 2014). Importantly, the SC events are often the precursors to strong geomagnetic storms.…”
Section: Discussion: a Possible Mechanism Of Ip Shock Impact On The Gmentioning
confidence: 99%
“…As an example, the destruction of the New Zealand power system transformer reported by Béland and Small (2004) coincided with a SC. Disturbances with dB/dt > 100 nT/min can occur during SC in the auroral region, and the magnitude of the SC-associated dB/dt is not necessarily related to the intensity of the following magnetic storm (Fiori et al 2014).…”
Section: Introductionmentioning
confidence: 99%